PENINGKATAN KEAMANAN DATA RAHASIA MENGGUNAKAN KRIPTOGRAFI DATA ENCRYPTION STANDARD PADA STEGANOGRAFI AUDIO BERFORMAT MP3 - Afriyadin Afriyadin; Sutardi Sutardi; LM. Fid Aksara (semanTIK, 2016)
Information can be something very precious and needs to be kept confidential. One of the solutions in securing information is to cryptography and steganography. Steganography is the art and science which studies data hiding on a medium such that its presence is not detected by the other party is not entitled to that information, whereas cryptography is a technique to encode (encryption) a secret data into encrypted data is incomprehensible.Steganography method Least Significant Bit (LSB) or low bit coding is a simple method of hiding data in the process, namely by replacing bit less important / least significant bit of each sampling point MP3 filewith a series of binary bits of hidden data. Mathematically LSB perform the conversion value of the lowest bit MP3 samples with values message bits to be inserted.Cryptography algorithm Data Encryption Standard (DES) was adopted by NIST (National Institute of Standards and Technology) a US Federal information processing standards. Generally DES divided into three groups, namely key processing, 64-bit data encryption and decryption of data 64 bits in which a group of interacting with each other.The system in this research was built using steganography method Least Significant Bit (LSB), a cryptography algorithm Data Encryption Standard (DES) and the Java programming language.Keywords— Steganography, LSB,MP3, Cryptography, DES, Java